Peningkatan Hasil Belajar Siswa melalui Metode Inkuiri di MIS Gampong Mutia - Rina Purnama Sari (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Langsa, 2021)
The activeness of students in learning is of course very necessary because by activating their five senses, they will learn more meaningfully. One of the teaching methods that can activate students' five senses is the inquiry method. The purpose of this study was to describe the increase in science learning outcomes at MIS Gampong Mutia. The design of this study used a control group posttest design. The instrument used is a test of learning outcomes for the material structure and function of plant parts. The results showed that there was an increase in science learning outcomes in classes that applied the inquiry method. So it can be said that this guided inquiry method is appropriate for use on the material structure and function of plant parts